2018
DOI: 10.1039/c8sm00921j
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable spheroidal hydrogel particles for cell and drug encapsulation

Abstract: The need to better mimic native tissues has accompanied research in tissue engineering and controlled drug delivery. The development of new platforms for cell and drug encapsulation followed the same trend, and studying the influence of the delivery material system's geometry has been gaining momentum. Aiming to investigate how an increase in surface area and varying particle shape could impact drug release and cell viability, a novel method was developed to produce spheroidal hydrogel particles with adjustabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
(31 reference statements)
0
21
0
Order By: Relevance
“…One such example is the potential of using spheroid particles generated by squeezing chitosan droplets between two superamphiphobic surfaces, followed by UV-crosslinking, to increase the release rate of encapsulated BSA. BSA was encapsulated in the particles and faster release was observed from spheroids than from spheres, shown in Figure 3 [64].…”
Section: Hybrid Hydrogels Incorporating Microstructuresmentioning
confidence: 98%
See 3 more Smart Citations
“…One such example is the potential of using spheroid particles generated by squeezing chitosan droplets between two superamphiphobic surfaces, followed by UV-crosslinking, to increase the release rate of encapsulated BSA. BSA was encapsulated in the particles and faster release was observed from spheroids than from spheres, shown in Figure 3 [64].…”
Section: Hybrid Hydrogels Incorporating Microstructuresmentioning
confidence: 98%
“…The benefits of anisotropic microparticles, such as spheroids, ellipsoids, rods, and disks, also have been shown to extend to hemodynamic settings, with both theoretical modeling and experimental studies indicating better margination, wall interaction, and adhesion [65]. The enhancement of both diffusion and cell viability (demonstrated by the incorporation of spheroid particles) [64], as well as the potential hemodynamic transport benefits arising from anisotropic particles, suggests the potential of employing more complex and anisotropic particles in hybrid hydrogels. Non-circular micropatterned regions in hybrid hydrogels have also been shown to increase the absorption of toxins, thus increasing the detoxification efficacy of these materials [66].…”
Section: Hybrid Hydrogels Incorporating Microstructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were also assessed numerically, in which the drug release rate was computed for different spheroidal-like geometries. 43 In another study, Wang et al, discovered the effect of applied voltage, on the morphology of electrospun zein protein fabrics. They reported that these protein fabrics formed either flat sheets or self-rolled tubes when immersed in water on the application of different voltage.…”
Section: Shape and Morphologymentioning
confidence: 99%